2015
DOI: 10.1038/srep16665
|View full text |Cite
|
Sign up to set email alerts
|

The AP-3 adaptor complex mediates sorting of yeast and mammalian PQ-loop-family basic amino acid transporters to the vacuolar/lysosomal membrane

Abstract: The limiting membrane of lysosomes in animal cells and that of the vacuole in yeast include a wide variety of transporters, but little is known about how these proteins reach their destination membrane. The mammalian PQLC2 protein catalyzes efflux of basic amino acids from the lysosome, and the similar Ypq1, −2, and −3 proteins of yeast perform an equivalent function at the vacuole. We here show that the Ypq proteins are delivered to the vacuolar membrane via the alkaline phosphatase (ALP) trafficking pathway,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 40 publications
(62 reference statements)
0
31
1
1
Order By: Relevance
“…This finding triggered the proposition of the so-called 'ALP pathway', in which Vps41 at the trans-Golgi regulates the formation of ALP-containing vesicles that traffic directly to the vacuole (Cowles et al, 1997a). Over the past few years, additional cargoes for the ALP pathway have been identified, which are all vacuolar membrane proteins (Llinares et al, 2015;Anand et al, 2009).…”
Section: Box 3 Insights From Yeastmentioning
confidence: 99%
“…This finding triggered the proposition of the so-called 'ALP pathway', in which Vps41 at the trans-Golgi regulates the formation of ALP-containing vesicles that traffic directly to the vacuole (Cowles et al, 1997a). Over the past few years, additional cargoes for the ALP pathway have been identified, which are all vacuolar membrane proteins (Llinares et al, 2015;Anand et al, 2009).…”
Section: Box 3 Insights From Yeastmentioning
confidence: 99%
“…Biosynthetic vacuolar 55 cargoes initially move from the ER to the Golgi. Some vacuolar membrane proteins traffic directly 56 from the Golgi to the vacuole with the aid of the Golgi-associated AP-3 adaptor complex (Cowles 57 et al, 1997;Odorizzi et al, 1998;Llinares et al, 2015). By contrast, CPY and certain other 58 vacuolar hydrolases first traffic from the Golgi to PVE compartments (Vida et al, 1993;Conibear 59 and Stevens, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Instead, we determined that both Pds1 and Esp1 are targeted to the vacuole using the ALP pathway. Although the ALP pathway is named because of the substrate initially described in this pathway (alkaline phosphatase), other proteins such as the vacuolar amino acid transporters Ypq1, Ypq2 and Ypq3 also require components of this pathway (45). We found that inhibition of the ALP pathway causes cells to adapt faster in response to a persistent DSB.…”
Section: Discussionmentioning
confidence: 83%